2022
DOI: 10.1108/jima-12-2021-0404
|View full text |Cite
|
Sign up to set email alerts
|

Food shopping during the COVID-19 pandemic: an exploratory study in four Near Eastern countries

Abstract: Purpose During a pandemic, risk and uncertainty are the most important factors affecting consumer behavior. Near Eastern marketplaces are undergoing dramatic change during the COVID-19 global pandemic. As a result, this paper aims to investigate the impact of COVID-19 on food shopping habits in four countries of the Near East sub-region, namely, Lebanon, the Palestinian territories, Oman and Qatar. Design/methodology/approach The research is based on an online survey conducted on 1,456 subjects using a snowb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Referring to the fruit and vegetable supply chain in Meknes (Morocco), Saidi et al [137] observed that the crisis prompted the emergence of new and more sustainable food supply methods, such as mutualized and local sourcing, as well as reduced food waste, leading the move towards sustainability. [165]; AlTarrah et al [121]; Belton et al [208]; Ben Hassen et al [145]; Ben Hassen et al [6]; Ben Hassen et al [141]; Dimassi et al [127]; Elgammal et al [171]; Ghali-Zinoubi [183]; Hamade [130]; Kaitibie et al [146]; Saidi et al [137]; Saidi et al [138]; Sobaih and Moustafa [179]; Sundarakani and Onyia [193]; Taybeh et al [119]; Zainal et al [124] 25 (16.55%) Consumption (including food services and food waste)…”
Section: Agriculture Subsectors and Food Chain Stagesmentioning
confidence: 99%
See 3 more Smart Citations
“…Referring to the fruit and vegetable supply chain in Meknes (Morocco), Saidi et al [137] observed that the crisis prompted the emergence of new and more sustainable food supply methods, such as mutualized and local sourcing, as well as reduced food waste, leading the move towards sustainability. [165]; AlTarrah et al [121]; Belton et al [208]; Ben Hassen et al [145]; Ben Hassen et al [6]; Ben Hassen et al [141]; Dimassi et al [127]; Elgammal et al [171]; Ghali-Zinoubi [183]; Hamade [130]; Kaitibie et al [146]; Saidi et al [137]; Saidi et al [138]; Sobaih and Moustafa [179]; Sundarakani and Onyia [193]; Taybeh et al [119]; Zainal et al [124] 25 (16.55%) Consumption (including food services and food waste)…”
Section: Agriculture Subsectors and Food Chain Stagesmentioning
confidence: 99%
“…The pandemic also affected the marketing and distribution of agri-food products. Several studies report increased recourse to food delivery and e-commerce for food procurement during the pandemic [6,73,77,130,135,156].…”
Section: Agriculture Subsectors and Food Chain Stagesmentioning
confidence: 99%
See 2 more Smart Citations
“…This research is considered important because previous research related to online shopping behavior during the COVID-19 pandemic in the psychological theme focused on negative variables such as depression (Di Crosta et al, 2021), or related to positive perceptions and attitudes of using technology (Alhaimer, 2021;Polas, Tabash, Jahanshashi, & Ahamed, 2022;Sumi & Ahmed, 2022), or trust issues (Ben Hassen, El Bilali, & Allahyari, 2022). This research Rahardjo, Pranandari, Putri, Qomariyah, Rini, & Andriani: Understanding the…….…”
Section: Introductionmentioning
confidence: 99%